The telobox, a Myb-related telomeric DNA binding motif found in proteins from yeast, plants and human. - Bilaud, T (1996)
The yeast TTAGGG binding factor 1 (Tbf1) was identified and cloned through its ability to interact with vertebrate telomeric repeats in vitro. We show here that a sequence of 60 amino acids located in its C-terminus is critical for DNA binding. This sequence exhibits homologies with Myb repeats and is conserved among five proteins from plants, two of which are known to bind telomeric-related sequences, and two proteins from human, including the telomeric repeat binding factor (TRF) and the predicted C-terminal polypeptide, called orf2, from a yet unknown protein. We demonstrate that the 111 C-terminal residues of TRF and the 64 orf2 residues are able to bind the human telomeric repeats specifically. We propose to call the particular Myb-related motif found in these proteins the 'telobox'. Antibodies directed against the Tbf1 telobox detect two proteins in nuclear and mitotic chromosome extracts from human cell lines. Moreover, both proteins bind specifically to telomeric repeats in vitro. TRF is likely to correspond to one of them. Based on their high affinity for the telomeric repeat, we predict that TRF and orf2 play an important role at human telomeres.